The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1363459320976746
|View full text |Cite
|
Sign up to set email alerts
|

Medicalisation, suffering and control at the end of life: The interplay of deep continuous palliative sedation and assisted dying

Abstract: Medicalisation is a pervasive feature of contemporary end of life and dying in Western Europe and North America. In this article, we focus on the relationship between two specific aspects of the medicalisation of dying: deep continuous palliative sedation until death and assisted dying. We draw upon a qualitative interview study with 29 health professionals from three jurisdictions where assisted dying is lawful: Flanders, Belgium; Oregon, USA; and Quebec, Canada. Our findings demonstrate that the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…45 The results indicated that PS is sometimes perceived as something belonging to the sphere of assisted dying, but probably more so in Quebec (Canada) and Flanders (Belgium) than in Oregon (USA). 45 The researchers argue that, to a significant degree, this may be related to the fact that assisted dying in Oregon can be self-administered, occurring mostly without the involvement of health professionals beyond lethal prescribing. On the other hand, physicians' involvement with assisted death in Quebec and Flanders is “practical” and continues until death.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…45 The results indicated that PS is sometimes perceived as something belonging to the sphere of assisted dying, but probably more so in Quebec (Canada) and Flanders (Belgium) than in Oregon (USA). 45 The researchers argue that, to a significant degree, this may be related to the fact that assisted dying in Oregon can be self-administered, occurring mostly without the involvement of health professionals beyond lethal prescribing. On the other hand, physicians' involvement with assisted death in Quebec and Flanders is “practical” and continues until death.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, physicians' involvement with assisted death in Quebec and Flanders is “practical” and continues until death. 45 The authors conclude that, regardless of the country where the participants were interviewed, the relief of suffering emerges as a concept- key in both PS and assisted death, however, both interventions can also be perceived as a way to exacerbate suffering. 45 It is important to note that, according to the European Association for Palliative Care, “in terminal sedation the intention is to relieve intolerable suffering, the procedure is to use a sedating drug for symptom control and the successful outcome is the alleviation of distress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Bereaved study participants in Ireland spoke of the vigil as a significant time of farewell, through '…its reciprocity or mutuality', suggesting its importance to all parties (Donnelly & Battley, 2010: 98). Dying is often described as medicalised, with professional institutions and practitioners having an over-influential role in decision making and orchestrating the end of life (Koksvik et al, 2020). The vigil is one possible way of attempting to reclaim dying on behalf of both the family and the dying person, and as a way of affirming bonds in readiness for the post-death period (Valentine, 2007).…”
Section: The Deathbed Vigilmentioning
confidence: 99%